Exploring the potential mechanisms and future trends of industrial eco-efficiency: a case study of coastal China - Sun, Yixuan; Zhang, Teng; Zhang, Baolei; Yin, Le; Wang, Jingjing (Frontiers in Environmental Science, 2024)
The industrial economy occupies a crucial position in China’s national economy, and industrial eco-efficiency (IEE) as a significant indicator of regional green development levels. Balancing the positive interaction between industrial economy and resource environment, and enhancing ecological efficiency in industrial development are vital for achieving sustainable regional economic development. This study measures the IEE of 115 cities in coastal China based on panel data of industrial resources and the environment factors. Subsequently, it further analyzes the influencing mechanisms and future trends of IEE. The results indicate that the overall IEE in coastal China is on an upward trend, with higher efficiency values in provinces and regions characterized by faster economic development and better environmental conditions. Significant changes in spatial patterns are observed, with the gaps between cities narrowing and a “multi-core” development model emerging. Factors such as per capita GDP, the ratio of industrial pollution control investment to GDP, innovation index, the proportion of foreign direct investment to GDP, and industrial labor productivity significantly positively influence IEE. In contrast, the proportion of industrial added value to GDP, urbanization rate, and the number of industrial enterprises exhibit notable negative inhibitory effects. Moreover, the interaction effect between industrialization level and other factors is most significant. In the future, IEE is expected to continue improving, although the sustainability of these changes appears weak. These findings reveal the potential impact mechanisms of resource consumption and environmental pollution caused by industrial activities on economic benefit output. This study provides a scientific basis for optimizing energy development layout, enhancing the comprehensive utilization of energy resources, and improving ecological compensation and protection mechanisms.